G309(P) New child protection body maps: Design to implementation. (27th April 2016) - von Stempel, C; Hann, G; Fertleman, C
Abstract : Background: Good documentation when performing a child protection medical is essential. The RCPCH's Child Protection Companion recommends the use of a proforma to standardise assessment and record keeping as well as to aid report writing. Included within medical record keeping is the practice of 'body mapping' where injuries are recorded on a line drawing. There is limited availability of sample body maps and no standardisation of views provided. Anecdotally many clinicians have commented that they would prefer anatomically positioned body maps with views of areas not previously covered such as the crown and axilla. Aim: The design and implementation of anatomically positioned, age appropriate and gender specific body maps. Method: The authors held a focus group of consisting of 12 paediatric trainees to discuss what paediatric doctors need from body maps. The artist produced the first draft body maps based on the focus group's suggestions. Four months later, the focus group was reconvened to examine the first drafts. Based on the feedback from the second focus group, the body maps were redrafted. Three named doctors for child protection were then asked for their feedback on the body maps produced. The artist then finalised the body maps. The final drafts were then tested in an acute trust which has a high burden of child protection issues and subsequent feedback led to the production of the body maps presented here. Results: The focus group wanted body maps to be anatomically positioned and to depict four age ranges: baby, toddler, young child, and teenager. They also wanted the young child and teenage body maps to be gender specific. The focus group also highlighted that they wanted specific maps for commonly injured body areas: hands, feet, head, ears, eyes, axilla, mouth including the frenulum and genitalia. An example body map is presented here (diagram 1). Conclusions: Body maps are an essential part of child protection medical record keeping and anatomically positioned body maps aid doctors to record injuries quickly and accurately.